Neurofibromatose de von Recklinghausen e feocromocitoma maligno: apresentação de três casos. - A Ventura; J Ribeiro; A Murinello; L Amado; A Morgado; C Guerra; F Murinello; J L Silva; J A Mota (Acta Médica Portuguesa, 1989)
Neurofibromatosis may involve every organ. Manifestations vary greatly and different kind of neoplasia may be associated with excessive frequency; it's the case of pheochromocytoma that, as a benign tumor, coexists in 10%. Description of coexistency as a malignant tumor is a rarity; therefore, we think it's interesting to publish our experience. Nevertheless the association of Von Recklinghausen's disease with hypertension is not always dependent of that kind of association.